Hubungan Tingkat Pengetahuan Karang Taruna Desa Tentang Cedera Otak Sebelum dan Sesudah Penyuluhan di Desa Pesisir Senggigi - Bambang Priyanto; Rohadi Muhammad Rosyidi; Januarman Januarman; Decky Aditya Zulkarnaen; Ahmad Taufik S; Bayu Tirta Dirja (Universitas Mataram, 2022)
Brain injury has the third largest prevalence of other injuries in Indonesia. Most brain injuries occur on highways as a result of motorcycling accidents. The only effective way to reduce the death rate from brain injury that occurs in motorcycle accidents is to wear a helmet. Cases of brain injury due to traffic accidents are often found in adolescents because of the lack of understanding of the importance of helmet use. Therefore, education is needed about the importance of using standard helmets when driving among teenagers. The counseling activity was carried out in one of the senior high schools (SMA) in Mataram with the dominant target of teenagers using motorized vehicles. The selected high school is SMA Negeri 2 Mataram. The method of implementing this counseling is by giving lectures on brain injury, the mechanism of trauma and brain injury and the importance of using standard head protective equipment (SNI helmets), playing videos about head trauma and interactive dialogue. The mandatory output that will be produced is in the form of research articles in the Unram Medical Journal. In addition, research results will be reported back to related fields as input and study material for traffic safety program activities in determining policies in planning, implementing, and evaluating programs as well as coordinating with related programs and sectors. The researcher will also provide a banner stand regarding the importance of using standard helmets for motorcycle riders at the activity location which can then be used as a medium of communication, information and education to the school students.